2017
DOI: 10.1016/j.neo.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 Inhibitor SCH900776 Effectively Potentiates the Cytotoxic Effects of Platinum-Based Chemotherapeutic Drugs in Human Colon Cancer Cells

Abstract: Although Chk1 kinase inhibitors are currently under clinical investigation as effective cancer cell sensitizers to the cytotoxic effects of numerous chemotherapeutics, there is still a considerable uncertainty regarding their role in modulation of anticancer potential of platinum-based drugs. Here we newly demonstrate the ability of one of the most specific Chk1 inhibitors, SCH900776 (MK-8776), to enhance human colon cancer cell sensitivity to the cytotoxic effects of platinum(II) cisplatin and platinum(IV)- L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Moreover, the combination of the platinum compound, cisplatin and the CHK1 inhibitor, rabusertib did not have a toxic effect on non-tumorigenic breast tissue-derived cells, which suggests that the high efficacy of the combination of CHK1 inhibitors and DNA-damaging agents is restricted to cancer cells. A similar antiproliferative effect was observed for PARP inhibitors, reinforcing the concept that inhibition of CHK1 allows cells to enter apoptosis when a relevant genetic instability is present, in this case due to alterations of DNA repair mechanisms or an increase in DNA damage [25]. Therefore, we found that agents that induced DNA damage, like gemcitabine or platinum compounds or to a less extent doxorubicin and topotecan, were synergistic in breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the combination of the platinum compound, cisplatin and the CHK1 inhibitor, rabusertib did not have a toxic effect on non-tumorigenic breast tissue-derived cells, which suggests that the high efficacy of the combination of CHK1 inhibitors and DNA-damaging agents is restricted to cancer cells. A similar antiproliferative effect was observed for PARP inhibitors, reinforcing the concept that inhibition of CHK1 allows cells to enter apoptosis when a relevant genetic instability is present, in this case due to alterations of DNA repair mechanisms or an increase in DNA damage [25]. Therefore, we found that agents that induced DNA damage, like gemcitabine or platinum compounds or to a less extent doxorubicin and topotecan, were synergistic in breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 83%
“…As shown in Figure 7, p53 pathway proapoptotic proteins, such as p53, Bax, cytochrome C, and caspase-3 were upregulated, while the anti-apoptotic Bcl-2 expression was decreased. P53, a major regulator in CDDP-induced cancer cell apoptosis57 via a transcription-dependent or independent pathway. Increased Bax can rupture the outer mitochondrial membrane to induce the cytochrome C release to activate the generation of caspase-3 and ultimately induces extrinsic apoptosis, while downregulated Bcl-2 leads to the intrinsic apoptosis through reduced formation of Bcl-2/Bax heterodimers which promotes the cytochrome C release for the initiation of apoptosis through caspase activation 58.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has shown that p53 serves as a key tumor suppressor, which is essential for induction of cisplatin-induced apoptosis ( Yang et al, 2012 ). It has been proposed that the presence of functional p53 facilitates the cytotoxic effects of chemotherapeutic drugs including cisplatin ( Herudkova et al, 2017 ). For instance, in head and neck squamous cell carcinoma, small molecules targeted p53-reactivation have been shown to induce apoptosis and enhance chemotherapeutic cytotoxicity ( Roh et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%